Dengue Hemorrhagic Fever (DHF) Risk Assessment for Gorontalo Regency in Indonesia Using Geographic Information System - Pakaya, Ririn; Hano, Yanti Hz.; Olii, Muhammad Ramdhan (Nusantara Science and Technology Proceedings, 2021)
Inadequate planning, housing, water, sewage, and waste management in urban and semi-urban areas produced ideal conditions for dengue viruses and their mosquito vector Aedes Aegypti to spread throughout the region over the preceding decade. Dengue prevention is primarily focused on vector control (chemical spraying, biological control, physical removal of breeding grounds, and infrastructure enhancement) and community education in the absence of a vaccine. They have not influenced the prevalence of Dengue Hemorrhagic Fever (DHF) Public health surveillance is the systematic and continuous collection of data and information on events, health problems, and conditions that influence the occurrence and spread of disease to plan, implement, and evaluate public health practices. It is crucial in dengue management since it determines the number and distribution of cases, viral serotypes, and severity of disease in a community. The purpose of this article is to examine the use of Geographic Information Systems (GIS) to determine the spatial distribution of the DHF Risk map in the Gorontalo Regency. The GIS system's overlay operation is utilized to combine two maps, namely the DHF hazard map and the DHF vulnerability map. The findings reveal that the Gorontalo Regency is dominated by low-risk classes, with a total area of 99,716.7 ha (46.52%). The GIS approach might be used to assess transmissible DHF risk zoning, which would aid in enhancing DHF and other vector-borne disease surveillance strategies to promote prevention and control efforts.